Electrospun PLA/PBS/MWCNT nanocomposite fibers for high-performance air filtration: A sustainable approach - Phiriyawirut, Manisara; Wangtanapat, Prin; Chanthanchumpunon , Apiwit; Phanchaweng, Ratchanon (Journal of Applied Research on Science and Technology (JARST), 2025)
For the development of high-performance air filtration materials, electrospun polylactic acid (PLA)/polybutylene succinate (PBS) blend fibers, reinforced with multi-walled carbon nanotubes (MWCNTs), were fabricated and subjected to comprehensive characterization. A PLA/PBS blend, at a 95/5 wt% ratio, was prepared through the dissolution of the constituent polymers in a dichloromethane/dimethylformamide mixture, using a 3:1 v/v ratio at a 17 wt% concentration. MWCNTs were introduced into the polymer solution, with dispersion facilitated by a Triton X-100 surfactant and ultrasonication, at concentrations ranging from 0 to 4 wt%. Electrospinning was performed under optimized conditions, specifically an applied voltage of 16 kV and a tip-to-collector distance of 18 cm. Upon the incorporation of MWCNTs, minor alterations to fiber morphology were observed, including a slight increase in fiber diameter and an enhancement in the uniformity of surface pore distribution. Thermal properties were analyzed, revealing a trend of decreasing glass transition temperature, melting temperature, and thermal stability as the MWCNT content increased. Mechanical properties were evaluated, with improvements in tensile strength and Young’s modulus documented with increasing MWCNT content. Filtration efficiency was assessed, and significant enhancements were achieved, with performance comparable to N95 masks (98-99%) recorded. Notably, a reduction in pressure drop across the filters was observed with increasing MWCNT content, indicating improved breathability. The potential of these biodegradable and environmentally sustainable nanocomposite fibers as an alternative to conventional filtration materials, addressing the growing concerns surrounding air pollution, is demonstrated by these results. This study highlights the feasibility of employing biopolymers and carbon nanomaterials for a more sustainable approach to air filtration, offering a viable solution for developing advanced, eco-friendly filtration technologies.